Grades of poorly differentiated clusters are associated with lymph node and the tumour, node and metastasis stages in colorectal carcinoma - Kerisnon@Krishnan, Thanamogan; Wan Yaacob, Wan Azura; Mohtarrudin, Norhafizah; Hussin, Huzlinda (Penerbit Universiti Sains Malaysia, 2023)
Background: Colorectal carcinoma (CRC) is the third most common cancer globally. In Malaysia, CRC is most prevalent among males and the second most common cancer among females. The CRC arises mainly from the adenocarcinoma sequence. Poorly differentiated clusters (PDCs) and tumour budding (TB) are believed to represent sequential steps in tumour growth. Therefore, this study analysed the association between PDC grades with clinicopathological and demographic characteristics of CRC. Methods: A total of 47 CRC cases previously diagnosed by histopathological examination were reviewed for the presence of PDCs and graded accordingly. The association between PDC grades with clinicopathological and demographic characteristics was statistically analysed. Results: Out of the 47 cases with PDCs, most of them were of grade 3 (G3) (n = 27, 57.4%), followed by grade 2 (G2) (n = 13, 27.7%) and grade 1 (G1) (n = 7, 14.9%). Higher PDC grades (G2 and G3) were mainly observed in higher tumour stage (T); T3 (n = 26, 83.9%), T4 (n = 12, 92.3%), N1 (n = 20, 86.9%), N2 (n = 15, 100%). In addition, there was a significant association between PDC grades with the nodal stage (N) (P = 0.013) and the tumour, node and metastasis (TNM) stages (P = 0.012). Conclusion: The PDC grades are useful for assessing the disease prognosis in CRC. A statistically significant association between PDC grades with N and TNM stages suggested that PDC grades are potential predictive parameters for invasive and metastatic risks in CRC.